Kualitas Digitalisasi dalam Pelayanan Kepada Masyarakat di Desa Setupatok - Urbaningrum, Rexy Nakula; Nurhadiansyah, Nurhadiansyah; Agustin, Depriana; Yulianti, Sastria; Fathiya, Dina Nurul (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
This research explores the potential of the community in building an independent village as well as the management of natural and human resources to become a more advanced and modern village society. This study uses a mix method, which is an approach that combines qualitative and quantitative approaches. The data obtained is based on the experience of the community and the perception of the village apparatus regarding the existing service system, through interviews and the distribution of questionnaires to the community and village officials. The results of this research are in the form of a prototype containing suggestions for future village development, including a prototype of a tourism village website and village social media as a means of information and digital services. It is hoped that this prototype can be a solution in improving the efficiency and accessibility of public services in Setupatok village. The purpose of this study is to measure the level of digitalization efficiency in public services in Setupatok village, measure the extent of the application of digitalization in the village, this research is also carried out as a form of service within the scope of the community, developing student potential in encouraging the progress of a village.